Construction of prediction intervals for the multiplicative Holt-Winter's methods - Arugay, Estela Blancaflor
The multiplicative Holt-Winters Exponential Smoothing Procedure is a useful procedure for forecasting. The point forecast is easily computed from a clearly defined equation. the interval forecsat, on the other hand, is not easily computed since the standard error of forecast is not easily computed. The Root Mean Square Prediction Error (RMSPE) is commonly used in lieu of the standard error of forecast: (μk±zₐ ̷₂RMSPE). A prediction interval based on the bootstrap is proposed as alternative to the one using RMSPE. This addresses the non-normal distribution of forecast especially with non-linear models. This prediction interval was evaluated using coverage probability. Results indicate that it performs well for data with clear trend and strong seasonality.